Acoustic Emission Measurement by Fiber Bragg Grating Glued to Cylindrical Sensor Holder - Sasaki, Toshinori; Iwata, Satoshi; Kadono, Akira; Kobayashi, Yuuki; Takahashi, Yoshimasa; Saitoh, Kenichi; Hisada, Shigeyoshi; Takuma, Masanori; Murata, Atushi (Advances in Materials Science and Engineering, 2014)
Fiber Bragg grating (FBG) is an optical fiber sensor and is suitable for acoustic emission (AE) measurements of structures such as chemical plants that require water resistance, explosion proofing, and so forth, However, directionality has been a problem in conventional usage which glues the grating range of an FBG to the inspection surface. This study proposes a cylinder-FBG (C-FBG) sensor with the FBG glued to a cylindrical sensor holder. Effectiveness of the sensor was evaluated by characterizing directionality and frequency sensitivity of the sensor and by comparing the detected AE signals in a 3-point bending test of a carbon fiber reinforced plastic (CFRP) laminate against a conventional wide-band piezoelectric AE sensor. The features of the detected signals were similar to the signals detected by the wide-band AE sensor. These results show that it is possible to produce a wide-band cylindrical sensor without the directionality limitations of the conventional usage of FBG.